The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/hbm.25260
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes at 6 months are related to brain structural and white matter microstructural reorganization in idiopathic tinnitus patients treated with sound therapy

Abstract: This study aimed to explore brain structural and white matter microstructural reorganization in the early stage of tinnitus and identify brain alterations that contribute to its relief after 6 months of sound therapy. We studied 64 patients with idiopathic tinnitus, including 29 patients who were categorized into an effective group (EG) and 35 who were categorized into an ineffective group (IG) according to the 6‐month follow‐up improvement of the Tinnitus Handicap Inventory score, along with 63 healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 47 publications
2
33
0
1
Order By: Relevance
“…Our latest study proved that idiopathic tinnitus patients with different outcomes (effective or ineffective) after sound therapy experienced distinct brain structural reorganization (Chen et al, 2021a). Thus, the main objective of this study was met by providing convincing data about whether the different prognoses of tinnitus patients after sound therapy can be associated with the differences in brain network connectivity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our latest study proved that idiopathic tinnitus patients with different outcomes (effective or ineffective) after sound therapy experienced distinct brain structural reorganization (Chen et al, 2021a). Thus, the main objective of this study was met by providing convincing data about whether the different prognoses of tinnitus patients after sound therapy can be associated with the differences in brain network connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have applied brain alterations to predict therapeutic outcomes or even screen patients before sound therapy (Chen et al, 2021a; Han, Yawen, et al, 2019; Han, Na, et al, 2019). For example, (Han, Yawen, et al, 2019; Han, Na, et al, 2019) used neural network nodes to predict the improvements in patient symptoms after sound therapy and found that features of the bilateral thalami were the best indicators, with adjusted AUC values of under 0.8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations